3D printed biaxial stretcher compatible with live fluorescence microscopy. (April 2020) - Shiwarski, Daniel J.; Tashman, Joshua W.; Eaton, Amity F.; Apodaca, Gerard; Feinberg, Adam W.
Graphical abstract: Abstract: Mechanical characterization and tensile testing of biological samples is important when determining the material properties of a tissue; however, performing tensile testing and tissue stretching while monitoring cellular changes via fluorescence microscopy is often challenging. Additionally, commercially available cell/tissue stretchers are often expensive, hard to customize, and limited in their fluorescence imaging compatibility. We have developed a 3D printed Open source Biaxial Stretcher (OBS) to be a low-cost stage top mountable biaxial stretching system for use with live cell fluorescence microscopy in both upright and inverted microscope configurations. Our OBS takes advantage of readily available open source desktop 3D printer hardware and software to deliver a fully motorized high precision (10 ± 0.5 µm movement accuracy) low cost biaxial stretching device capable of 4.5 cm of XY travel with a touch screen control panel, and an integrated heated platform with sample bath to maintain cell and tissue viability. Further, we designed a series of tissue mounts and clamps to accommodate varying samples from synthetic materials to biological tissue. By creating a low-profile design, we can directly mount the stretcher onto a microscope stage, and through coordinated biaxial stretching we maintain a constant field of view facilitating real-time sample tracking and time-lapse fluorescence imaging.